2023
DOI: 10.3390/su15065257
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Model for the Continuous Intention to Use Metaverse Technology in Higher Education: A Case Study from Oman

Abstract: This paper investigates adopting metaverse in academic institutions based on a conceptual model. The proposed conceptual model was created to empower future perspectives of the metaverse system. Even though the metaverses system was just recently launched, few attempts have been made to evaluate its impact on the educational sector. This paper attempted to determine the impact of metaverse system by providing a conceptual model that encompasses innovativeness, context awareness, perceived enjoyment, ubiquity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Results showed that in the "metaverse-based learning environment, PU, PE, and PEU" were all reliable predictors of IU. Salloum, et al [61] found that originality has a significant role in determining the success of the metaverse system. However, it seems that the role of perceived ubiquity in encouraging the usage of the metaverse system is less successful than first thought.…”
Section: Key Factors That Influence Individuals' Intentions To Use An...mentioning
confidence: 99%
“…Results showed that in the "metaverse-based learning environment, PU, PE, and PEU" were all reliable predictors of IU. Salloum, et al [61] found that originality has a significant role in determining the success of the metaverse system. However, it seems that the role of perceived ubiquity in encouraging the usage of the metaverse system is less successful than first thought.…”
Section: Key Factors That Influence Individuals' Intentions To Use An...mentioning
confidence: 99%
“…In previous research endeavours, scholars have delved deep into the potential of the metaverse within the educational landscape, exploring a diverse array of experiences. Notable works by [10][11][12][13] underscore this focus. A distinct study by [14] pivoted around the importance of Augmented Reality (AR) within the educational context.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…According to Prakash et al (2023), Metaverse can transform traditional teaching methodologies by increasing student engagement and retention of information through collaborative learning, experiential learning, customized learning, and gamification. These elements provide a sense of pride and achievement when students complete tasks or reach educational breakthroughs (Salloum, 2023). Many authors have studied how Metaverse changes education (Lin et al, 2022;Prakash, 2023;Hwang et al, 2023) and the numerous benefits, including interaction, authenticity, and portability.…”
Section: Metaverse Contemporary Developmentmentioning
confidence: 99%